Characterisation of allelochemical compounds signature in two mangrove forest species of Rhizophora apiculata and Acrostichum aureum and potential in suppressing weed growth - Othman, Rashidi; Ramya, Razanah; Mohd Hassan, Norazian; Wan Daud, Wan Masyitah; Johari, Nursyafica Nadia (IOP Publishing, 2019)
Rhizophora apiculata and Acrostichum aureum are a common mangrove species in Malaysia. Allelochemical interaction of the mangrove species was speculated to play an important role in dominance in the harsh mangrove environment. This study assessed the quantitative and qualitative determination for total phenolic content and individual phenolic compounds as allelochemical content for R. apiculata and A. aureum leaves as a potential allelopathic substance. The second objective is to investigate the allelopathic effect towards weed germination and growth through in vitro model system. Two types of maceration extraction comprising water extraction and sequential alkaline extract were used for allelochemical screening analysis. Both extractions were separated by ethyl acetate. Acrostichum aureum had the highest total phenolic content (1129.52 μg GAE/g DW) in comparison with R. apiculata. Meanwhile, the quantitative analysis by HPLC, revealed that different extraction detected different individual phenolic acid, Caffeic acid detected in both mangrove species in sequential alkaline extraction by A. aureum. The allelopathic effect of Chloris barbata for A. aureum extract indicated that during pre-emergent development, the suppression of weed growth was higher compared to post-emergent. Therefore, A. aureum may work as an allelochemical producer and can contribute to the establishment of pure colonies of A. aureum in the mangrove ecosystem